Desenvolvimento da competência argumentativa em um curso para futuros professores de Ciências Biológicas - Lima Filho, Adalberon Moreira de (2019)
In this thesis we approach the development of Argumentative Competence (AC) in a course offered to future teachers of Biological Sciences (BS), from a Federal Public Institution. AC is one of the essential Scientific Competencies (SC) for CB students to develop Scientific Thinking (ST). We believe that working with Argumentation in the initial teacher education of CB is one of the didactic strategies that can contribute to the development of the CA of them and their future students, so we decided to investigate the following question: is it possible to develop the CA of future teachers? of CB from a training course using Argumentative Didactic Sequences (ADS)? The research is justified by the need to develop scientific and technological knowledge and scientific skills and competences (SC) that will contribute to the formation of future teachers of BS. Argumentation is a didactic science strategy that enables the construction, elaboration and development of the AC and the development of the ST, necessary for teacher training and practice. The general objective of the research was to verify if from a training course offered to future teachers of SB, with the use of ADS, it is possible to develop the AC. The specific objectives were: to point out the contributions of ADS as strategy and didactic resource for the initial formation of future teachers of SB; identify possible advances in the development of AC of these future teachers after the completion of a training course. Our research hypothesis was that the use of argumentation as a didactic strategy can facilitate this process and contribute to the development of AC of future SB teachers. We defend the thesis that through a teacher education course using ADS as a didactic strategy, it is possible to contribute to the development of AC and, consequently, to the improvement of teacher education and SB teaching. The research was guided by the qualitative approach of the intervention type and was developed in three stages: exploratory (79 students), intervention (15 students) and evaluation (9 students). For data analysis we used the content analysis technique and the Toulmin's Argument Pattern (TAP) Model. The results of the research, collected through observations and the textual production of the students, showed that the ADS elaborated for the offered course contributed to develop the AC of the future teachers of CB; that the problem situations used in the classes favored their SC development. The ADS used in the intervention research allowed the construction of AC in the students, which confirms our hypothesis and our thesis.